2000
DOI: 10.2460/ajvr.2000.61.1534
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine kinetics in dogs with experimentally induced renal vascular hypertension

Abstract: Increased blood pressure during the hypertensive period was likely attributable to increased NE spillover rate, which resulted in a significant increase in plasma NE concentration. Analysis of these results suggests that central sympathetic outflow was increased and may be responsible for the pathogenesis of high blood pressure during the acute phase of renal vascular hypertension in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Since the pioneering work of a canine model of renal vascular hypertension was reported by Goldblatt et al 8 many methods, for example, the snare, 517 cuff, 18 or single-hole clip, 19 have been used to induce hypertension in large animals for different purposes. However, few of these methods have been used to induce arterial plaque formation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the pioneering work of a canine model of renal vascular hypertension was reported by Goldblatt et al 8 many methods, for example, the snare, 517 cuff, 18 or single-hole clip, 19 have been used to induce hypertension in large animals for different purposes. However, few of these methods have been used to induce arterial plaque formation.…”
Section: Discussionmentioning
confidence: 99%
“…In rats both one-kidney, oneclip and two-kidney, one-clip hypertension are associated with elevated plasma norepinephrine levels [65]. In twokidney, two-clip hypertensive dogs, plasma catecholamine concentrations and norepinephrine spillover rate were significantly increased [66]. Based on MSNA recordings and measurements of total body norepinephrine spillover several [67 -69] but not all studies [27] found elevated sympathetic activity in patients with renovascular hypertension.…”
Section: Renovascular Hypertension and Angiotensin IImentioning
confidence: 98%
“…The extracellular volume expansion induced by anuria is the main pathophysiological determinant of hypertension in hemodialysis patients (10). In addition, the norepinephrine concentration in dogs with experimentally induced renal vascular hypertension tends to increase (11). Therefore, it seems likely that hypertension in renal dysfunction dogs was induced by extracellular volume expansion and changes in sympathetic nervous activity.…”
mentioning
confidence: 99%